Kepuasan kerja sebagai variabel mediasi pada pengaruh stres kerja terhadap niat keluar - Stanlie Andrian Noeary; Albert Kurniawan Purnomo; Fotuho Waruwu (Universitas Kristen Maranatha, 2020)
This research is motivated by the high turnover among Y and Z generation caused by the level of. work stress caused by workload and unclear work procedures. This study aimed to determine job satisfaction as a mediator of the relationship between work stress and turnover intention. This study used quantitative methods with full sampling and respondents as many as 65 employees. The data analysis technique was performed using SEM test with WarpPLS 7.0 software. Based on the test, results showed that work stress has a significant effect on turnover intention and job satisfaction is evident to be intervening variable.